A Simple Method to Measure Serum Lactate Concentration as A Reliable Parameter to Detect Flaps Blood-flow Patency - Handayani, Siti (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: The change in !ap blood flow patency can be monitored by measures. Subjective clinical observation through flap examinations is greatly biased depending on examiner’s experience. Standardised equipments of assessment are more reliable. This study propose the use of a device to provide an objective, safe,reproducible, simple, portable, and cost-effective method of monitoring flaps vitality by measuring serum concentration of lactic acid. Methods: An experimental lab-based study was conducted utilising Sprague-Dawley rats. Twenty rats were randomly assigned into two groups. In all subjects, bilateral groin-flaps were elevated. In rats of Group A, the vein pedicle of one-side of the flap was occluded while in Group B both the artery and vein on one-side of the flap were occluded. The other side of flaps in each rat were left unoccluded to serve as controls. Baseline serum lactate was measured in all flaps, then remeasured 60 and 120 minutes in all flaps after pedicle manipulations. Results: The mean lactate concentration of Group A rats with vein-occluded !aps was 2.5 ± 0.17 mmol/L at 0-min initially, and increased to 7.9 ± 0.16 mmol/L 120-min after occlusion (p<0.0005). The mean lactate concentration of Group B rats with arterial and venous flap occlusion was 2.55 ± 0.21 at baseline, which increased four-fold at 120-min to 9.86 ± 0.28 mmol/L (p<0.0005). Among the two groups, the lactate difference was also found to be significant. Conclusion: This study demonstrates that the proposed method detects serum lactate changes in flaps with vein and arteriovenous occlusions. This thus can be used as an objective parameter to evaluate compromised blood flow on cutaneous flaps.